Highly efficient synthesis of C3-symmetric O-alkyl substituted triphenylenes and related Mannich derivatives. Issue 16 (17th July 2018) - Berton, Giacomo; Borsato, Giuseppe; Zangrando, Roberta; Gambaro, Andrea; Fabris, Fabrizio; Scarso, Alessandro
Abstract : C 3 -Symmetric tris-benzyl- O -substituted hexahydroxytriphenylene (HHTP ) was prepared through selective ring opening with DIBAL-H in 48% yield (38% fromHHTP in a two-step synthesis). Abstract : C 3 -Symmetric tris-benzyl- O -substituted hexahydroxytriphenylene (HHTP ) was prepared through selective ring opening with DIBAL-H in 48% yield (38% fromHHTP in a two-step synthesis) avoiding the use of noxious, expensive and limited market availability reagents, with complete recovery of the undesired C s co-product that is quantitatively recovered and converted back intoHHTP . The C 3 -symmetric triphenylene product was further functionalized through substitution, deprotection and Mannich condensation reactions affording a series of C 3 -symmetric functionalized scaffolds in good yields for supramolecular applications.